USING GOOGLE EARTH™ AND GEOGRAPHICAL INFORMATION SYSTEM DATA AS METHOD TO DETECT URBAN SPRAWL AND GREEN SPACES FOR BETTER WELL BEING CASE OF A COASTAL LANDSCAPE - Boussema, Safa Bel Fekih; Allouche, Faiza Khebour; Bekaoui, Ameni; Khalifa, Yosra; M’Sadak, Houda (International Journal of Research -GRANTHAALAYAH, 2020)
Coastal landscapes are facing a huge challenge to manage the spatial extension of their built-up area at the expense of the reduction of natural and cultivated areas. This is the case of Hergla city, located in the southern part of Hammamet Gulf, Tunisia. This paper firstly highlights changes of LULC in Hergla city, between 2007 and 2017 using a supervised classification of Landsat images. The evolution of built-up area between 2002 and 2020 is examined expending Google Earth images. Lastly, the geolocalization of green spaces are provided. Then, the superposition of all these analyzes will be used to propose a landscaping for a better human well-being. Finally, this research indicates the importance of analyzing LULC change at multiple scales; it revealed that built-up area has been increased and olive fields reduced from 64 % in 2007 to 30.2 %in 2017. It shows, too, an important urban expansion from 39.9 Ha in 2002 to 48.3 Ha in 2020. However, the green spaces are concentrated in the North and middle part of the city and a proposal for the development of an urban park on the south side will help to balance the spatial distribution of green spaces in this area and ensure better human well-being.